Analisis Implementasi Assesment pada Pembelajaran Inklusi di SDN Cibodas 1 Kota Tangerang - Nurfadhillah, Septy; Erdian, Ahmad Edo; Marcelino, Ragil; Widyastuti, Tri; Afianti, Nundung Ari; Sabila, Roudhotus; Yanti, Annisa Ardhana; Efendi, Herlina (MASALIQ, 2022)
This study aims to determine the implementation of inclusive education at SDN Cibodas 1 Tangerang. This research type and methodology uses qualitative case studies. The research subjects were principals, special supervision teachers and therapists. Data was collected by using observation, interview and recording techniques. Data analysis was done by data triangulation technique. The school organizes inclusive education by conducting an assessment of prospective students with Special Needs in collaboration with the Tangerang City Education Office, with the aim that it is seen as a material that determines the type of educational service that is appropriate and based on the needs and abilities of students. teachers with special educational backgrounds Training with regular teachers. Special facilities and infrastructure for Children with Special Needs This school already has treatment rooms, assessment tools, treatment tools and learning media. To create a friendly school environment for children with special needs, schools create programs that communicate with the community, parents, and the government. These programs use the 2013 curriculum which has been modified to better meet their needs. This includes funds for Children with Special Needs and PBB which are used in the same way for regular and inclusive schools as well as using BOS for funds for special supervised teachers and Honor therapists. However, the funds are not the same between regular schools and inclusive schools even though the needs are different. This is because some of the facilities and infrastructure are not adequate for children with special needs.